(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
All patterns of the objective world are reflected in the categories of human knowledge. The categories of modern man’s thinking are the product of a long historical development. Their content changes as a person’s knowledge of objective reality deepens [Panfilov 1971: 3].